2021
DOI: 10.2106/jbjs.cc.20.00435
|View full text |Cite
|
Sign up to set email alerts
|

Gustilo IIIA Open Bimalleolar Fracture Dislocation of Ankle with Ipsilateral Achilles Tendon Rupture

Abstract: Case: Although rare, a medial malleolus fracture plus ipsilateral Achilles tendon rupture has been described in previous case reports. We present a unique case of an open bimalleolar fracture dislocation with ipsilateral Achilles tendon rupture after a motorcycle crash. His Achilles injury was diagnosed intraoperatively during external fixator placement. He presented in a delayed fashion to our institution, where he underwent open reduction internal fixation and Achilles tendon reconstruction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For example, a previous study reported that the quality of healing after conservative treatment is poor, and the possibility of breaking again is also high [ 9 ]. Meanwhile, the side effect of CT is known to be limited, while the recovery period is too long [ 10 ]; the recovery period of MS is relatively short, and the side effect of MS is less obvious compared with OS [ 4 , 11 ]. According to these studies, MS appears to be more conducive to the rupture and healing of the Achilles tendon, with less surgical injury and faster postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study reported that the quality of healing after conservative treatment is poor, and the possibility of breaking again is also high [ 9 ]. Meanwhile, the side effect of CT is known to be limited, while the recovery period is too long [ 10 ]; the recovery period of MS is relatively short, and the side effect of MS is less obvious compared with OS [ 4 , 11 ]. According to these studies, MS appears to be more conducive to the rupture and healing of the Achilles tendon, with less surgical injury and faster postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of the literature showed that medial malleolar fracture is the most frequent ankle fracture associated with Achilles tendon rupture followed by lateral malleolus [2,8,[10][11][12]14,15,18,20]. There is only one bimalleolar ankle fracture with concurrent Achilles tendon rupture reported, in which the tendon injury was missed on the initial evaluation and diagnosed intra-operatively [19]; however, in our patient, the fact that there was an obvious wound over the Achilles rupture site deceived us from suspecting the presence of ankle fracture. An obvious clinical diagnosis of Achilles tendon rupture is also reported as one of the reasons for the misdiagnosed ankle fracture in this group of patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature revealed only fifteen single cases of ankle fractures associated with Achilles tendon rupture have been reported. Among these, 12 reported cases of Achilles tendon rupture were associated with medial malleolar fracture [6][7][8][9][10][11][12][13][14][15][16][17], 2 cases of Achilles tendon rupture were in combination with lateral malleolar fracture, [2,18] and only 1 case of acute Achilles tendon rupture with ipsilateral open bimalleolar ankle fracture was reported [19].…”
Section: Introductionmentioning
confidence: 99%